2022
DOI: 10.1002/hec.4564
|View full text |Cite
|
Sign up to set email alerts
|

A theory of fiscal policy response to an epidemic

Abstract: Governments worldwide have issued massive amounts of debt to inject fiscal stimulus during the COVID‐19 pandemic. This paper analyzes fiscal responses to an epidemic, in which interactions at work increase the risk of disease and mortality. Fiscal policies, which are designed to borrow against the future and provide transfers to individuals suffering economic hardship, can facilitate consumption smoothing while reduce hours worked and hence mitigate infections. We examine the optimal fiscal policy and characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Policy interventions to maintain economic growth are therefore preferable. During GHEs, governments must coordinate their efforts to manage working time arrangements and determine the optimal level of public debt based on production technology and disease characteristics to effectively implement fiscal policy [ 69 ]. Simultaneously, medium- and long-term structural policies must be launched while establishing epidemic risk assessment tools.…”
Section: Discussionmentioning
confidence: 99%
“…Policy interventions to maintain economic growth are therefore preferable. During GHEs, governments must coordinate their efforts to manage working time arrangements and determine the optimal level of public debt based on production technology and disease characteristics to effectively implement fiscal policy [ 69 ]. Simultaneously, medium- and long-term structural policies must be launched while establishing epidemic risk assessment tools.…”
Section: Discussionmentioning
confidence: 99%
“…Kocherlakota (2022) finds that fiscal policy helps to achieve macroeconomic stabilization better in a model with public debt bubble. Pang (2022) examined the optimal fiscal policy for improved social welfare, following the COVID-19 pandemic. The authors found that the optimal fiscal response is contingent on production technology and the severity and transmissibility of the pandemic.…”
Section: Empirical Literaturementioning
confidence: 99%